2005
DOI: 10.1159/000082573
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology: Just Cool or a Real Tool?

Abstract: Telemedicine is the practice of healthcare using interactive audio, visual and data communication. This includes healthcare delivery, diagnoses, consultation and treatment as well as education and transfer of medical data. The transmission of multimedia streams has remained a major challenge. Although the Internet remains basically insecure, technology allows today to define and implement complete security profiles for specific (medical) communities. Data security is a must as in all other areas of applied med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 31 publications
0
26
0
4
Order By: Relevance
“…Nevertheless, these studies have shown the usability and the feasibility of these new devices in teledermatology [1][3]. In fact, the unique aspect of mobile teledermatology is that this system might become a filtering or triage system allowing a more sensible approach for the management of patients with emergent skin diseases [1][5]. In addition, mobile teledermatology may also become a powerful screening tool for malignant cutaneous tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these studies have shown the usability and the feasibility of these new devices in teledermatology [1][3]. In fact, the unique aspect of mobile teledermatology is that this system might become a filtering or triage system allowing a more sensible approach for the management of patients with emergent skin diseases [1][5]. In addition, mobile teledermatology may also become a powerful screening tool for malignant cutaneous tumors.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, the results of the present study suggest that telemedicine may be useful for obtaining second opinions in programmes to control leprosy. Because store-and-forward telemedicine allows a case discussion to be generated, 21,22 it may also contribute to greater involvement of primary care physicians and improved collaboration between medical colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…During the last years, teledermatology has gained a lot of interest among scientific community. It can deeply revolutionize the delivery of dermatology services, providing equitable services to remote areas and allowing primary care physicians to refer patients to well-equipped dermatological services at a distance [3]. Teledermatology uses telecommunication technologies to transfer information to patients via mobile phone and images of skin lesions to clinicians via the Internet.…”
Section: Introductionmentioning
confidence: 99%